Interactive transcriptome analysis of malaria patients and infecting Plasmodium falciparum - Yamagishi, Junya; Natori, Anna; Tolba, Mohammed E.M.; Mongan, Arthur E.; Sugimoto, Chihiro; Katayama, Toshiaki; Kawashima, Shuichi; Makalowski, Wojciech; Maeda, Ryuichiro; Eshita, Yuki; Tuda, Josef; Suzuki, Yutaka (Genome Research, 2014)
To understand the molecular mechanisms of parasitism in vivo, it is essential to elucidate how the transcriptomes of the human hosts and the infecting parasites affect one another. Here we report the RNA-seq analysis of 116 Indonesian patients infected with the malaria parasite Plasmodium falciparum (Pf). We extracted RNAs from their peripheral blood as a mixture of host and parasite transcripts and mapped the RNA-seq tags to the human and Pf reference genomes to separate the respective tags. We were thus able to simultaneously analyze expression patterns in both humans and parasites. We identified human and parasite genes and pathways that correlated with various clinical data, which may serve as primary targets for drug developments. Of particular importance, we revealed characteristic expression changes in the human innate immune response pathway genes including TLR2 and TICAM2 that correlated with the severity of the malaria infection. We also found a group of transcription regulatory factors, JUND, for example, and signaling molecules, TNFAIP3, for example, that were strongly correlated in the expression patterns of humans and parasites. We also identified several genetic variations in important anti-malaria drug resistance-related genes. Furthermore, we identified the genetic variations which are potentially associated with severe malaria symptoms both in humans and parasites. The newly generated data should collectively lay a unique foundation for understanding variable behaviors of the field malaria parasites, which are far more complex than those observed under laboratory conditions.
10.1101/gr.158980.113